Pembuatan Asap Cair (Liquid Smoke) dari Limbah Serbuk Kayu Jati dan Kayu Pinus secara Pirolisis sebagai Pengawet Alami - Nurul Izza; Alfian Putra; Zuhra Amalia (Politeknik Negeri Lhokseumawe, 2022)
Research on making liquid smoke from teak and pine sawdust by pyrolysis which will be used as a natural preservative. Pine and teak sawdust carried out a pyrolysis process for 4 hours at a temperature of 400 oC using a pyrolysis reactor with a maximum capacity of 2 kg. The ratio of teak wood powder raw material: pine wood used 1:0; 0:1 and 1:1. Then purified by distillation with a distillation temperature of 100, 101-125, 126-150 oC. Liquid smoke application is used on tofu food with observation time of 2, 3, 4, 5 and 6 days. The quality of the liquid smoke produced is a mixture of sawdust and teak (1:1) at a distillation temperature of 126-150 oC, namely pH 3.1, density 1.028 g/mL and the clearest color and able to preserve food for up to 4 days.